One-Pot Synthesis of Organic Disulfides (Disulfanes) from Alkyl Halides Using Sodium Sulfide Trihydrate and Hexachloroethane or Carbon Tetrachloride in the Poly(ethylene glycol) (PEG-200) - Abbasi, Mohammad; Mohammadizadeh, Mohammad Reza; Moosavi, Hekmat; Saeedi, Narges (Synlett, 2015)
Symmetric disulfides are produced by treating their corresponding organic halides including benzylic, allylic, primary and secondary halides with Na2S·3H2O and C2Cl6 or CCl4 in PEG-200 at room temperature in high yields.
Keywords: disulfides; alkyl halides; sodium sulfide; C2Cl6; CCl4; thiols